Ecuador Potato Wholesaler Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
Ecuador potato wholesaler survey is the study of the wholesalers in the potatoes value chain in Ecuador. These data allow quantifying the extent of food loss at the wholesaler level using consistent approaches that are comparable across commodities and regions. They also enable characterizing the nature of food loss, specifically the production stages and the particular processes at which loss is incurred.